MAGNETIC SCANNING OF PRECAMBRIAN ROCKS CRYSTALLINE BASEMENT AVERAGE POBUZHYE (FOR EXAMPLE DOMEN GAIVORON-ZAVALIE) AND IT’S INFORMATIVITY - RESHETNYK, M.; SUKHORADA, A.; KHOMENKO, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The new concept of ultradetailed complex magnetometer researches on Precambrian rocks crystalline basement is offered and developed. On the basis of the received results the structurally-geological analysis of magnetic sources of Precambrian rocks on Average Pobuzhya of the Ukrainian crystalline basement is carried out. It is established that anomalies of a magnetic field are connected with a bodies of evlisites. An abnormal magnetic field is produce the evlisites with are expansion by forms of stratum or interlayer.